The Agricultural Routing Planning in Field Logistics - Utamima, A.; Reiners, Torsten; Ansaripoor, Amir Hossein; Seyyedhasani, H. (IGI Global, 2018)
The agricultural sector is facing the need to gain a higher yield on their fields while optimising their operations to stay competitive and satisfy the continuously increasing demand for produce. Cost reductions can be achieved by increasing the effective field size and reducing the operations without gain (e.g., driving longer distance to harvest the field). The agricultural routing planning (ARP) problem represents a specialisation of the travelling salesman problem (TSP) or vehicle routing problem (VRP) with focus on the agricultural operations and considerations of the field and vehicles configurations. In addition, various adaptations of the problem can be found in the literature that define a new problem class with specialised optimisation needs. This chapter introduces the ARP and reviews the past and current research and developments.